MEMAKNAI KEMISKINAN: PERAN KELEMBAGAAN DALAM MENANGGULANGI LINGKARAN SETAN KEMISKINAN - Budi Rajab (Jurnal Masyarakat dan Budaya, 2006)
Initially, the cause of poverty has something to do with the lack of control of economic resources. This then brings about the so-called the â€œculture of povertyâ€ and lack of capabilities, that is indicated, among other, by dependent and fatalistic attitudes, which in the end tend to reinforce and perpetuate the initial condition, i.e., the lack of control of economic resources. Thus, it is not surprising, then, that the causes and effects of poverty seem to be a vicious circle. Poverty alleviation strategies and programs aim at raising people capabilities and changing the culture of poverty, as implemented by the former New Order regime, have resulted in far below the expectation, only a few of poor people have alleviated from their unfortunate condition. Moreover, as the effect of these strategies and programs, it creates the so-called â€œrelative povertyâ€ which refers to the widening gap and inequality in income distribution and control over (economic) resources among the population. Given these complexities, the structural approach proposes to develop a special institutional arrangementâ€”a body that will tackle the poverty alleviation workâ€”whose strategy is to give the poor a direct access and control over the economic resources. This body shall be made available down to the local level, i.e. municipality and district levels. To get the strategies and programs effective in eradicating poverty, effort to change of the culture of poverty and to raise people capabilities are that of important and, consequently, still have to undertake. Kata kunci: kemiskinan, budaya kemiskinan, lingkaran setan kemiskinan, kelemahan strategi penanggulangan kemiskinan, dan pembangunan kelembagaan penanggulangan kemiskinan